2022
DOI: 10.3390/membranes12111057
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Analysis in One-Stage Ultrafiltration of Precipitation-Treated Bacillus subtilis Fermentation Liquors for Biosurfactant Recovery

Abstract: Primary recovery of surfactin from precipitation-pretreated fermentation broths of Bacillus subtilis ATCC 21332 culture by one-stage dead-end and cross-flow ultrafiltration (UF) was studied. Dead-end experiments were first performed to select suitable conditions, including the amount of added ethanol—a micelle-destabilizing solvent (0–70 vol%), type (polyethersulfone, polyacrylonitrile, poly(vinylidene fluoride)) and molecular-weight cut-off (MWCO, 30–100 kDa) of the membrane in the surfactin concentration ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although both centrifugation and UF could remove microorganism cells, the removal rate of UF (86%) was higher than that of centrifugation (53%) [ 58 ]. Some researchers have carried out a study on the recovery of surfactin from fermentation broths in cross-flow UF by using PES UF membranes [ 59 ]. The results showed that the recovery rate of surfactin could reach 75% in the UF process.…”
Section: Technology For Routine Water Purification Based On Nanofiber...mentioning
confidence: 99%
“…Although both centrifugation and UF could remove microorganism cells, the removal rate of UF (86%) was higher than that of centrifugation (53%) [ 58 ]. Some researchers have carried out a study on the recovery of surfactin from fermentation broths in cross-flow UF by using PES UF membranes [ 59 ]. The results showed that the recovery rate of surfactin could reach 75% in the UF process.…”
Section: Technology For Routine Water Purification Based On Nanofiber...mentioning
confidence: 99%
“…For this purpose, various membrane techniques can be used. It has been widely documented that the complete retention of microbial cells, proteins, and other molecules can be achieved by microfiltration (MF) [8][9][10] and ultrafiltration (UF) [11][12][13] processes. However, most organic compounds and salts present in fermentation broths have a low molecular weight (MW), hence, they may not be rejected effectively and sufficiently by the above-mentioned techniques.…”
Section: Introductionmentioning
confidence: 99%
“…As the most successful method, the concentrated fabrication and examination of high-performance membrane technologies has been foreseen. Miscellaneous membrane-dependent technologies, therefore, have been applied for water decontamination [ 3 , 4 ]. Usually, membrane technologies have been claimed for having low cost, fine workability, efficiency, low energy ingesting, and scale-up viabilities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%